The Effect of Structural Capital, Working Capital Management and Earnings Management on Financial Distress - Hassa, Anandya Nur’alia; Azzardina, Aulia (InFestasi, 2024)
This study examines the effect of structural capital, working capital management, and earnings management on financial distress. The data used comes from the annual reports of retail companies, which were selected using the purposive sampling method. Multiple linear regression analysis was used to test the hypothesis. The results of the study indicate that earnings management has no effect on financial distress, but structural capital and working capital management have a positive effect on financial distress. These results support the resource-based theory, which states that company resources are unique and essential to achieving sustainable competitive advantage so that companies can identify key resources, innovation, differentiation through unique resources, and company reputation. However, if not done correctly, it will increase costs and bring the company into a state of distress. Further research is also expected to elaborate several theories that can support the results of the study. The results of this study can provide insight for companies in designing strategies to manage resources efficiently, reduce the risk of financial distress, and improve financial performance